Efforts to Reduce Psychological Problems in the Quarter Life Crisis Phase with Pastoral Accompaniment Methods - Albert Christiawan; Rudolf Weindra Sagala; Stimson Hutagalung; Rolyana Ferinia (Jurnal Teologi (JUTEOLOG), 2022)
The purpose of this research was to find out the importance of pastoral care for young people who are in the quarter life crisis phase. The method used is a survey with data collection techniques using questionnaires distributed to respondents and interviews. The sample used is non-probability sampling using the quota sample method. The number of questionnaires collected was 43 from the population of young people between 18-30 years of age. The results showed that some respondents agree that pastoral care is important for young people who were in the quarter life crisis phase. Some respondents of young people claimed that they needed pastoral accompaniment and trust the pastor's guidance and advice. However, there were still some of young people who feel they did not need pastoral care. This had the potential to cause problems when they went through the quarter life crisis phase.